1999
DOI: 10.4269/ajtmh.1999.61.951
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution and epidemiology of Oesophagostomum bifurcum and hookworm infections in humans in Togo.

Abstract: Abstract. In contrast to the rest of the world, infections with Oesophagostomum bifurcum are commonly found in humans in northern Togo and Ghana. In addition, infections with hookworm are endemic in this region. In the present study, a detailed map of the geographic distribution of O. bifurcum and hookworm infections in northern Togo was made. There were a number of foci with high prevalence of infection with O. bifurcum. All the villages examined were infected with hookworm, and the distribution was quite pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…In humans, T. trichiura infections are commonly more severe in young children than in adults in areas where the disease is endemic (Bundy et al 1987). Evidence also suggests that prevalence of O. bifurcum peaks in humans in Ghana during early adolescence (Pit et al 1999). Acquired immunity is among the possible mechanisms generating similar patterns in various primate host-nematode parasite associations.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, T. trichiura infections are commonly more severe in young children than in adults in areas where the disease is endemic (Bundy et al 1987). Evidence also suggests that prevalence of O. bifurcum peaks in humans in Ghana during early adolescence (Pit et al 1999). Acquired immunity is among the possible mechanisms generating similar patterns in various primate host-nematode parasite associations.…”
Section: Discussionmentioning
confidence: 97%
“…It is likely that human-human transmission is occurring in the endemic areas [37]. Further, in some locations no monkeys are present, thus suggesting that the parasite may not be an obligate zoonotic infection [36].…”
Section: Oesophagostomiasismentioning
confidence: 99%
“…The ®rst reports of infection in humans date back to 1905 [35], but in 1991 Polderman et al [36], reported that the parasite was commonly found in humans in Northern Togo and Ghana. Recent estimates indicate that in these areas over 230 000 individuals carry infection [37].…”
Section: Oesophagostomiasismentioning
confidence: 99%
“…recorded to date from non-human primates, O. bifurcum, O. stephanostomum, and O. aculeatum have also been reported in humans (Chabaud & Lariviere, 1958;Polderman & Blotkamp, 1995). Zoonosis caused by O. bifurcum is endemic in the northernmost part of Ghana and Togo situated in western Africa, and high prevalences of the disease in human residents have been recorded (Blotkamp et al, 1993;Polderman & Blotkamp, 1995;Pit et al, 1999;Yelifari et al, 2005;Gasser et al, 2006). Recently, however, multifaceted genetic analyses have demonstrated that different genotypes of O. bifurcum are prevalent in human patients and local non-human primates (Mona monkeys, Patas monkeys, Green monkeys, and Olive baboons) in Ghana and Togo (de Gruijter et al, 2004(de Gruijter et al, , 2005; reviewed by Gasser et al, 2006Gasser et al, , 2009, supporting parallel assump-HELMINTHOLOGIA, 51, 2: 83 -93, 2014 Prevalence and genetic diversity of Oesophagostomum stephanostomum in wild lowland gorillas at Moukalaba-Doudou National Park, Gabon tions based on epidemiological and morphological analyses de Gruijter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%